2019
DOI: 10.1108/jpmh-08-2018-0056
|View full text |Cite
|
Sign up to set email alerts
|

Are the early benefits of the Adoption Support Fund (therapeutic support for adoptive families) sustainable?

Abstract: Purpose The purpose of this paper is to explore the wider context in which the national evaluation of the Adoption Support Fund (ASF) was delivered and raise concerns about the sustainability of the early outcomes. Design/methodology/approach The paper briefly summarises the outcomes of a two-year mixed-methods evaluation. This included a two-wave postal survey (n=792) and follow-up (n=481), an online survey of adopters (n=586) and professionals (providers n=50, local authority staff n=124) and in-depth fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Although the Adoption Support Fund recognises the need for those adopting to receive support, this help has tended to be focused almost exclusively on the relationship between adopted child (or children) and parents (King, et al., 2017); the particular needs of adoptive couples seemed to be overlooked. This gap in support services should be addressed, since many couples struggle to manage their relationship and without support may be in danger of experiencing significant inter-parental conflict, separation or divorce, all of which have potentially damaging effects on children’s well-being (Harold, et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Adoption Support Fund recognises the need for those adopting to receive support, this help has tended to be focused almost exclusively on the relationship between adopted child (or children) and parents (King, et al., 2017); the particular needs of adoptive couples seemed to be overlooked. This gap in support services should be addressed, since many couples struggle to manage their relationship and without support may be in danger of experiencing significant inter-parental conflict, separation or divorce, all of which have potentially damaging effects on children’s well-being (Harold, et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The respective study methodologies of the Australian, Dutch, and English studies are reported elsewhere in greater detail (Goemans et al, 2018; King, Gieve, Iacopini, Hahne, & Stradling, 2017; Tarren-Sweeney, 2007; Tarren-Sweeney, 2013a). While general child protection practice in the three study locations are likely to be quite similar, there are some important differences in their care systems.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire consisted of questions regarding the foster child, the foster family, and the foster placement. The Dutch versions of the SDQ (Van Widenfelt, Goedhart, Treffers, & Goodman, 2003) and the BAC (Goemans et al, 2018; King et al, 2017) were used to measure foster children’s mental health. The child sample (4- to 11-year-old) consisted of 118 children, with a mean age of 7.80 ( SD = 2.15) and slightly more boys (56.4%) than girls (43.6%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These and other reasons led in 2015 to the establishment by the Department for Education (DfE), part of UK Government, of an Adoption Support Fund (ASF) for England to meet the therapeutic needs first of children who were adopted and later to include those who were cared for by special guardians. The children accessing a range of therapies through this funding have been identified as having very significantly elevated mental health needs compared with other children in the overall population (King et al, 2017; Burch et al, 2021), with 80–90% having needs in the clinical range (Burch et al, 2021). Similarly, the parents and special guardians caring for these children had significantly worse emotional wellbeing needs compared with the overall adult population (King et al, 2017; Burch et al, 2021).…”
Section: Introductionmentioning
confidence: 99%